New current relevance in Croatian: epistemic immediacy and the aorist - Stanojević, Mateusz-Milan (2007)
Traditional Croatian grammars (e.g. Katičić 1991: 57-59) describe the aorist as a general past tense used with perfective verbs, which denotes completed past. Moreover, the aorist is suggested to be stylistically marked, because it is primarily used in traditional narrative fiction. More recently some Croatian linguists have noted a sporadic use of the aorist as a ? generic past tense? in short text messages (Žic-Fuchs 2002-2003: 606) and as expressing recent past (e.g. Težak and Babić 1994: 265). Building on the points concerning the relationship between the aorist and the perfekt in Croatian put forward by Stanojević and Geld (2005), in this paper we claim that in its current usage the aorist expresses epistemic immediacy, i.e. the immediacy of the process in relation to the speaker and her knowledge about the event. The aorist is most frequently used in the first person singular, and it can refer to future, which indicates that it describes events in the epistemic region closest to the speaker? s vantage point (Langacker 1991). For instance, in: (1) Odoh u školu. go-aorist-1st sg in school. ? I am off to school.? the aorist denotes an action that coincides with the speech event or immediately follows it. The aorist also refers to an event that closely precedes the speech event: (2) Kako upravo rekoh? As just say-aorist-1st sg ? As I have just said? ? This is in contrast with the use of the perfekt, which usually refers to an earlier, more specific time frame: (3) Kako sam rekao prošle godine? As be- 1stsg-pres say-participle-sg-masc last year ? ? Like I said last year? ? Thus, we will attempt to show that the symbolic value of the aorist has come to denote actions in the speaker? s immediate dominion, which implies current relevance. In order to do this we selected six most frequent Croatian perfective verbs (doći ? come? , otići ? leave? , reći ? say? , vidjeti ? see? , dobiti ? get? and kupiti ? buy? ), based on a frequency dictionary of Croatian (Moguš, Bratanić and Tadić 1999). We used recent non-fictional texts from the Croatian National Corpus (www.hnk2.ffzg.hr) to identify their patterns of usage in the aorist and any differences from the usage of the perfekt. We found that the reemergence of the aorist is chiefly related to spoken language, as shown by the aorist occurring primarily in the first person singular, by its usage in relating spoken language, and by its tendency to refer to recent action. Based on these findings, we constructed an instrument to obtain grammaticality judgments and usage tendencies relating to the epistemic immediacy of the action in the aorist and the perfekt, which we used with 159 native speakers of Croatian. The aorist is systematically reported as a tense used to refer to epistemically immediate action by 70% of the participants, which corroborates our hypothesis. Thus, this research applies the theoretical framework of cognitive linguistics to design an empirically based procedure for linguistic investigation. These kinds of procedures are particularly important in investigating languages such as Croatian, where spoken corpora are not yet available.